How does Perceived Organizational Support Affect Psychological Capital? The Mediating Role of Authentic Leadership - Bilgeturk, Mahmut; Baykal, Elif (SCIENDO, 2021)
Background and Purpose: Authentic leadership, the most noteworthy positive leadership style accepted by positive organizational behavior scholars, is famous for its contributions to psychological capitals. And, in fact, this leadership style can flourish and be experienced more easily in situations where there are supportive organizational conditions. Hence, in this study, we assume that organizational support is an important antecedent for experiencing and displaying authentic leadership. Furthermore, in organizations wherein authentic leadership is practiced, people may assume organizational support comes about thanks to their leaders's management style, particularly where authentic leadership may shadow the effect of perceived organizational support on the psychological capitals of individuals. So, in our model we proposed that perceived organizational support will have a positive effect on both authentic leadership style and the psychological capitals of individuals. Moreover, authentic leadership will act as a mediator in this relationship. Design/Methodology/Approach: For the related field research we collected data from professionals working in the service sector in Istanbul. Related data have been analysed with structural equation modelling in order to test our hypotheses. Results: Results of this study confirmed our assumptions regarding the positive effects of perceived organizational support on authentic leadership and on four basic dimensions of psychological capital: self-efficacy, optimism, resilience, and hope. Moreover, our results confirmed the statistically significant effect of authentic leadership on psychological capital and partial mediator effect of authentic leadership in the relationship between perceived organizational support and psychological capital. Conclusion: Our results indicate the importance of empowering employees and engaging in authentic leadership behaviour in increasing psychological capitals of employees and psychologically creating a more powerful workforce.
Keywords: Perceived organizational support; Authentic leadership; Psychological capital; TEACHERS SELF-EFFICACY; SOCIAL SUPPORT; JOB-SATISFACTION; OPTIMISM; HOPE; ANTECEDENTS; RESILIENCE; HOPELESSNESS; HOPEFULNESS; PERSONALITY; Business & Economics